Pemanfaatan Limbah Kulit Nanas Menjadi Bioetanol dengan Variasi Konsentrasi Ragi dan Lama Fermentasi - Febri Liani Br Simanjuntak; Muhammad Yerizam; Anerasari Meidinariasty (Jurnal Serambi Engineering, 2024)
Pineapple peel waste can pollute the environment if not properly managed. On the other hand, pineapple peel waste can be used as a raw material for the production of bioethanol. The aim of this study was to evaluate the effect of variations in yeast concentration and the duration of the fermentation process on the bioethanol content of pineapple peel waste. In the fermentation process with variations in yeast concentration of 1.5%, 2% and 4%, the type of yeast used is Saccharomyces cerevisiae, the addition of nutrients in the form of NPK and urea by 0.5% each, as well as variations in the length of fermentation for 4 days, 5 days, 6 days, 7 days and 8 days. This study showed that the bioethanol content obtained was significantly influenced by yeast concentration and fermentation time. The sample with the highest ethanol content was produced with the addition of 4% yeast and fermentation for 5 days, the bioethanol content produced was 59% based on calculations using the standard ethanol curve equation and 57.23% based on analysis using GC-MS.